PENGEMBANGAN AWAL METODA PERHITUNGAN PADI 0.0 MODEL SEBARAN PERJALANAN BERBASIS DATA ARUS LALU LINTAS(Kasus Percobaan Sederhana 4 Zona, 4 Ruas, Sebaran Proporsional dan Pembebanan All-or-Nothing Murni) - Hitapriya Suprayitno (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2005)
Synthetic model development is always very laborious and complicated task. Therefore, a more practical modeling method based on traffic flow data is necessary. In general, this development task has practically never been tried in ITS. A first attempt has been done and provided a calculation method called Experimental Model PADI 0.0. The experiment showed that mathematically it was a Simultaneous Linear Equations (SLE) Case. This model was still very primitive and needed to be developed. Thisresearch was aimed to develop the Model PADI 0.0. A more complicated case, a proportional distribution case, had been taken for this attempt. The results indicated that the Model PADI 0.0 was valid to solve the experimental case. Furthermore, for the same transportation network model, the trip distribution pattern does not affect the SLE form. Afterward the experimental case still needed to be developed by integrating a more complicated traffic assignment model.